Health indicators in intellectual developmental disorders: The key findings of the POMONA‐ESP project. Issue 1 (27th June 2018) - Folch, Annabel; Salvador‐Carulla, Luis; Vicens, Paloma; Cortés, Maria José; Irazábal, Marcia; Muñoz, Silvia; Rovira, Lluís; Orejuela, Carmen; González, Juan A.; Martínez‐Leal, Rafael
Abstract: Background: The aim of this paper was to summarize the main results of the POMONA‐ESP project, the first study to explore health status in a large representative, randomized and stratified sample of people with intellectual developmental disorders in Spain. Methods: The POMONA‐ESP project collected information about the health of 953 individuals with intellectual developmental disorders. Results: Diseases such as urinary incontinence, oral problems, epilepsy, constipation or obesity were highly prevalent among the participants; with gender‐differentiated prevalences for certain conditions, and age and intellectual disability level as risk factors for disease. Overmedication was common in the sample, and drugs were often prescribed without any clinical indication or follow‐up. The present authors also found a lack of important relevant information about the participant's health and a lack of adequate genetic counselling. Conclusions: Our findings may contribute to a better understanding of health status and needs of people with intellectual developmental disorders and suggest several courses of action to improve their health care.